Feedback according to some biomechanical variables using visual aids and its impact on improving the performance of certain tennis skills - satar , hasna; maki, Ali (Journal of Physical Education, 2023)
Many scholars and researchers in the field of Physical Education study the factors and elements of physical, mechanical and psychological ... and other factors that have an active role in the educational process as to their impact in the field of learning skills as motor correct and ideal, as these factors play an important role in the learning process from beginners , learn skills in the game of tennis sources confirm the importance of always start teaching her gradually, and through the use of methods of modern educational which give positive effect in the speed of learning and mastery of form which does not lead to stability and not to forget.to learn any skill need to confined, the most important is the feedback, because the performance and the implementation of the skill requires the player to lead this skill repeatedly down to the automatic , through the control of movements and analyzed with the coach or self-analysis of those skills.The research problem; the trainers used in most cases means verbal to give direct feedback to the players, and in many of these cases does not emphasize the angles which achieved when you apply special skills and that can not appear from the coach to the player only by using technical means to help direct observation of what has been the performance by the player in order to enhance the player’s information correction associated with the performance and therefore can do the skills the economy of high-power and flow to good bring him the technical performance right and Outstanding Achievement, and believes the researchers of this type of nutrition will contribute to the achievement of good ,enhance the situation of training and learning when you apply Skills strike the front and back in tennis.The objectives of the research were:1 - identify the level of technical performance to blow the front and back in tennis.2 - Identify the impact of feedback, according to some variables bio –kinematics in the development of the performance level of skill strike the ground the front and back in tennis.The research hypotheses:1 - There are significant differences between the tests before and after both experimental and control groups.2 - There are significant differences between the post tests for the two sets of research in the variables under study for the experimental group.The most important conclusions appointed;1 - The emphasis on education after corrective information has ensured the evolution of the level of performance for a player better than the rest of the usual ways to learn the skill.2 - to practice accompanied by visual feedback according to mechanical conditions given the opportunity to gain skilled strike the front and rear and ensured the required accuracy in voltage requirements of less3 - to feedback additional worked to develop a sense of the experimental group gestures when weighted front and rear status preparatory and gave a positive effect on the evolution of performance to them after it was stressed that there should be suitable for the application of weighted least time possible and the importance of this to gain the required speed of the mechanical side.4 - The emphasis on achieving the goal of beating the application stage, by providing the joints to urge him to go